Beyond apical ballooning: computational modelling reveals morphological features of Takotsubo cardiomyopathy. Issue 14 (26th October 2019) - Pontecorboli, Giulia; Biglino, Giovanni; Milano, Elena Giulia; Sophocleous, Froso; Biffi, Benedetta; Dastidar, Amardeep Ghosh; Schievano, Silvia; Di Mario, Carlo; Bucciarelli-Ducci, Chiara
Abstract: Takotsubo cardiomyopathy (TCM) is characterized by transient myocardial dysfunction, typically at the left ventricular (LV) apex. Its pathophysiology and recovery mechanisms remain unknown. We investigated LV morphology and deformation in n = 28 TCM patients. Patients with MRI within 5 days from admission ("early TCM") showed reduced LVEF and higher ventricular volumes, but no differences in ECG, global strains or myocardial oedema. Statistical shape modelling described LV size (Mode 1), apical sphericity (Mode 2) and height (Mode 3). Significant differences in Mode 1 suggest that "early TCM" LV remodeling is mainly influenced by a change in ventricular size rather than apical sphericity.